Pojęcie samoświadomości w filozofii świadomości Paula Natorpa - Noras, Andrzej J. (Folia Philosophica, 2018)
The paper aims at presenting Paul Natorp’s views on consciousness discussed on historical and systematic plane. In the former case understanding of consciousness and self-consciousness is discussed in the context of Cohen’s views. In the latter the problem is conceived in the light of evolution of both concepts in Natorp.